2023
DOI: 10.1007/s11423-023-10209-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robot-assisted digital storytelling on hospitalized children’s communication during the COVID-19 pandemic

Abstract: This study proposed a robot-assisted digital storytelling approach to reduce hospitalized children's anxiety about intravenous injections and to improve their therapeutic communication and therapeutic engagement. In order to verify the effectiveness of the robot-assisted digital storytelling approach, a randomized controlled study was implemented. A total of 47 children from a regional hospital were randomly assigned to an experimental group (n = 21) and a control group (n = 26). The experimental group adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…All the included studies were published in the past ten years and were conducted across six countries. A total of 815 participants reported pain-related and affective outcomes during IV placement (5 studies [14][20] [21][29] [30] ), port needle insertion (1 study [31] ), flu vaccination (1 study [19] ), blood sampling (1 study [32] ) and dental treatment (2 studies [33][34] ). Almost all the children had underlying medical conditions with the exception of 34 healthy children in Beran's trial.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…All the included studies were published in the past ten years and were conducted across six countries. A total of 815 participants reported pain-related and affective outcomes during IV placement (5 studies [14][20] [21][29] [30] ), port needle insertion (1 study [31] ), flu vaccination (1 study [19] ), blood sampling (1 study [32] ) and dental treatment (2 studies [33][34] ). Almost all the children had underlying medical conditions with the exception of 34 healthy children in Beran's trial.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Several studies have demonstrated its positive impact on the development of skills such as computational thinking, critical thinking, problem solving, creativity, motivation, and metacognitive skills [34][35][36][37][38]. According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42]. Despite this, there is very little scientific literature analyzing the influence of ER on improving curricular content, especially bioscience content, and existing studies usually focus on improving the knowledge and skills related to the robot itself and its handling [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42]. Despite this, there is very little scientific literature analyzing the influence of ER on improving curricular content, especially bioscience content, and existing studies usually focus on improving the knowledge and skills related to the robot itself and its handling [40][41][42][43]. Benitti [44] and Ferrada [45] identified studies that presented the advantages of the use of ER in teaching content, including scientific content, at the Early Childhood Education stage [46], in Primary Education [47], or in Secondary Education [48].…”
Section: Introductionmentioning
confidence: 99%